A method for estimation of fundamental frequency for tonal sounds inspired on bird song studies - Jarne, Cecilia Gisele (2019)
In this work a simple implementation of fundamental frequency estimation is presented. The algorithm is based on a frequency-domain approach. It was mainly developed for tonal sounds and it was used in Canary birdsong analysis. The method was implemented but not restricted for this kind of data. It could be easily adapted for other sounds. Python libraries were used to develop a code with a simple algorithm to obtain fundamental frequency. An open source code is provided in the local university repository and Github. • The algorithm and the implementation are very simple and cover a set of potential applications for signal analysis.• Code implementation is written in python, very easy to use and modify.• Present method is proposed to analyze data from sounds of Serinus canaria.